2010
DOI: 10.1016/j.ejso.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI in clinically and mammographically occult breast cancer presenting with an axillary metastasis: A systematic review

Abstract: Please cite this article as: de Bresser J, de Vos B, van der Ent F, Hulsewé K. Breast MRI in clinically and mammographically occult breast cancer presenting with an axillary metastasis: a systematic review, European Journal of Surgical Oncology (2009Oncology ( ), doi: 10.1016Oncology ( /j.ejso.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 26 publications
0
56
2
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) has proven its promise in the detection of asymptomatic or occult breast lesions with high sensitivity [3,4,5]. MRI also provides valuable information for detecting multicentric breast cancer in women with dense breasts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has proven its promise in the detection of asymptomatic or occult breast lesions with high sensitivity [3,4,5]. MRI also provides valuable information for detecting multicentric breast cancer in women with dense breasts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ipsilateral axillary lymphadenopathy is the fi rst clinical symptom in 0.3-1.0 % of all breast carcinomas [ 60 ]. Buchanan et al investigated female patients with unilateral axillary lymphadenopathy without clinical or mammographic detection of a primary tumor in the breast and reported that contrast-enhanced MRI detected >50 % of these primarily occult breast carcinomas [ 47 ].…”
Section: Breast Cancermentioning
confidence: 98%
“…However, clinical examination, mammography, and US are not able to identify the cancer. MRI sensitivity for detecting unknown breast cancer ranges from 25% to 86% [14]. When MRI is positive, adequate surgical treatment consists of lumpectomy or mastecomy according to lesion size and location.…”
Section: Occult Primary Cancermentioning
confidence: 99%